INTERKONEKSI MULTIPEL LEVEL REPRESENTASI MAHASISWA CALON GURU PADA KESETIMBANGAN DALAM LARUTAN MELALUI PEMBELAJARAN BERBASIS WEB - Farida, Ida (2012)
This research aims to produce interconnection of multiple level representations (IMLR) using web-based model of learning and analyse its impact on increasing the ability of pre-service chemistry teachers. The model was developed through R & D design with three phases: preliminary study phase, model design and model validation. The design model validated by experts judgment, and limited tryout to 31 students, then performed a model revision. The revised model implemented to 37 students using quasi-experiments method: one group pretest-posttest design. The results showed that: 1) The model has characteristics to develop students IMLR ability through multimodal representations with assignments and probing questions, creating social climate and online assessment as feedback of learning performance; 2) Students IMLR ability increased in each topic of chemical equilibrium on aqueous solution. High category students have the highest IMLR ability. There is no differences ability between medium and low categories of students. Highest ability in acid-base equilibrium topic, and the lowest on buffer solution topic; 3) Students have better ability to resolve the problem with interconnection pattern starting from macroscopic to submicroscopic and symbolic rather than starting from submicroscopic to symbolic and macroscopic; 4) Students gave positive respond to the model. The model strength are: facilitate learning in multimodal representation, improve understanding of submicroscopic level, changing of problem solving abilities patterns of macroscopic-symbolic into six interconnection patterns and improve student learning patterns. Limitations of the model are: not adaptive in accessing web features, had less rapid feedback and lack of description of essay question scoring, depend on availability internet bandwidth and hosting capacity. It is suggested to: made learning adaptive, provides more question of varies interconnection pattern, develop a system of scanning key words and submicroscopic diagrams to facilitate essay questions scoring, developed model for other chemical topics, and finally institution should facilitate availability of hardware and internet networks with adequate bandwidth.